Cooperative robot and user friendly robot- new challenge in robotics - Rahman , Md Mozasser; Khan, Md. Raisuddin (2008)
In the near future many aspect of our life will be encompassed by tasks performing in cooperation with robot. The application of robot in home automation, agriculture production and medical operations etc will indispensable. As a result robot needs to be made human-friendly and to execute tasks in cooperation with human. Researchers proposed many new field of research in Robotics. Cooperative robotics and User friendly robotics are two new area of robotics research. Some researcher is trying to make human like robot. Robots that will be imitate human characteristics in movement, learning etc. Other researchers trying to develop robots which will be entertain human. Another group trying to develop robots and/or control system or robots those will be work cooperatively. In this paper it is tried to gather information regarding these two fields in brief.